Effects of Gradient Heating and Constant Temperature Sterilization on Volatile Substances of Zigong Cold Spicy Beef - LIU Bowen, ZHAO Bing, ZHAO Yan, ZHANG Shunliang, LIANG Erhong, LI Su, ZHANG Kaihua, XI Liqin, ZHANG Chen, ZHAO Xin (Shipin Kexue, 2025)
The effects of different thermal sterilization processes on the volatile flavor substances of Zigong cold spicy beef were determined by headspace solid phase microextraction (HS-SPME) combined with gas chromatography-mass spectrometry (GC-MS). In four groups: control (unsterilized), T1 (100 ℃ for 10 min, 110 ℃ for 25 min, and 121 ℃ for 8 min), T2 (100 ℃ for 10 min, 115 ℃ for 20 min, and 121 ℃ for 5 min), and T3 (121 ℃ for 10 min), a total of 54 volatile flavor substances were detected. The total contents of volatile substances in the control, T1, T2 and T3 groups were 1 280.11, 1 338.30, 935.31 and 686.47 μg/kg, respectively. The most abundant substances in cold spicy beef were olefins, aldehydes, ketones and alcohols. According to their odor activity values (OAVs), linalool, decylaldehyde and nonylaldehyde were identified as the most significant contributors to the flavor. Principal component analysis (PCA) showed clear separation between the three treatment groups and the control group, T1 being the closest to the control group. Consistently, the results of electronic nose and sensory evaluation showed that the flavor of the T1 group was more similar to that of the control group because sulfur-containing compounds in the T2 and T3 groups contributed more to the flavor, and the difference between them was not significant (P > 0.05). In summary, compared with traditional sterilization, T1 provided better maintenance of the flavor of cold spicy beef.